Development of urban intervention policies. ProMeBa Case in Mar del Plata - Gonzalez, Sofía Ariadna (2021)
The problem of informality and the formation of precarious settlements due to the development of urbanization, has been the object of the implementation of a set of social and urban policies that seek to alleviate the conflictive processes of increasing exclusion resulting from neoliberal policies. From this context, and understanding the relevance that space presents in social analysis, and the problem of difference and social and spatial segregation, this article proposes to investigate the formation of urban state interventions and their possible impacts, taking as case study the implementation of the Neighborhood Improvement Program -ProMeBa- in socio-spatially segregated neighborhoods in the city of Mar del Plata. The methodology used mainly assumes a qualitative approach where the review of specific antecedents such as documents, records, photographs and all those relevant data for the analysis of this study will be carried out.